2022
DOI: 10.1021/acsomega.2c05956
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Reactive Blue 4 Dye Removal by Lemon Peel Bead Doping with Iron(III) Oxide-Hydroxide and Zinc Oxide

Abstract: The increasing concern of dye contamination in wastewater results in the toxicity of aquatic life and water quality, so wastewater treatment is required to treat the low water quality standard for safety purposes. Lemon peel beads-doped iron(III) oxide-hydroxide (LBF) and lemon peel beads-doped zinc oxide (LBZ) were synthesized and characterized to investigate their crystalline structure, surface morphology, chemical compositions, chemical functional groups, and ζ potentials by X-ray diffraction, field emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…For material modifications, many previous studies have been reported for using a variety of metal oxides of iron (II or III) oxide (Fe 4 O 3 or Fe 2 O 3 ), zinc oxide (ZnO), titanium dioxide (TiO 2 ), aluminum oxide (Al 2 O 3 ), tin (IV) oxide (SnO 2 ), and magnesium oxide (MgO) to increase surface area and pore volume of adsorbents offering to increase lead or RB4 dye removal efficiency [6][7][8] . The modified materials of sugarcane bagasse with Fe 2 O 3 , sawdust with ZnO, and lemon peels with iron (III) oxide-hydroxide have been used for lead removal [8][9][10] , and the , bagasse with zinc oxide, and lemon peels beads with iron (III) oxidehydroxide have been applied for removing RB4 dye [11][12][13] . Moreover, the stability of the material is another point for applying industrial application, so the changing of material form from a powder form to a bead form in many studies has also been reported with supporting the increase of heavy metal or dye removal efficiencies [6][7][8][12][13][14] .…”
Section: Powdered and Beaded Sawdust Materials Modified Iron (Iii) Ox...mentioning
confidence: 99%
See 1 more Smart Citation
“…For material modifications, many previous studies have been reported for using a variety of metal oxides of iron (II or III) oxide (Fe 4 O 3 or Fe 2 O 3 ), zinc oxide (ZnO), titanium dioxide (TiO 2 ), aluminum oxide (Al 2 O 3 ), tin (IV) oxide (SnO 2 ), and magnesium oxide (MgO) to increase surface area and pore volume of adsorbents offering to increase lead or RB4 dye removal efficiency [6][7][8] . The modified materials of sugarcane bagasse with Fe 2 O 3 , sawdust with ZnO, and lemon peels with iron (III) oxide-hydroxide have been used for lead removal [8][9][10] , and the , bagasse with zinc oxide, and lemon peels beads with iron (III) oxidehydroxide have been applied for removing RB4 dye [11][12][13] . Moreover, the stability of the material is another point for applying industrial application, so the changing of material form from a powder form to a bead form in many studies has also been reported with supporting the increase of heavy metal or dye removal efficiencies [6][7][8][12][13][14] .…”
Section: Powdered and Beaded Sawdust Materials Modified Iron (Iii) Ox...mentioning
confidence: 99%
“…The modified materials of sugarcane bagasse with Fe 2 O 3 , sawdust with ZnO, and lemon peels with iron (III) oxide-hydroxide have been used for lead removal [8][9][10] , and the , bagasse with zinc oxide, and lemon peels beads with iron (III) oxidehydroxide have been applied for removing RB4 dye [11][12][13] . Moreover, the stability of the material is another point for applying industrial application, so the changing of material form from a powder form to a bead form in many studies has also been reported with supporting the increase of heavy metal or dye removal efficiencies [6][7][8][12][13][14] .…”
Section: Powdered and Beaded Sawdust Materials Modified Iron (Iii) Ox...mentioning
confidence: 99%
“…Since 1/n values of SBF and SBFB had less than 1 that meant both materials were favorable lead adsorptions. Moreover, both linear and nonlinear isotherm models were recommended to plot graphs for confirming the results and protecting against data mistranslation 45,[47][48][49][50] .…”
Section: Batch Adsorption Experimentsmentioning
confidence: 99%
“…The results demonstrated that q m and K L values of ZBF were higher than others, so it might have the highest lead removal efficiency than other zeolite A materials. Moreover, both linear and nonlinear isotherm models were recommended to plot graphs for confirming the results and protecting against data mistranslation [43][44][45][46][47][48][49][50] .…”
Section: Adsorption Isotherms the Adsorption Patterns Of Zeolite A Su...mentioning
confidence: 99%
“…The results illustrated q e and k 2 values of ZBF were higher than others, so it might have the highest lead removal efficiency with fast reaction than other zeolite A materials. Finally, the graph plotting of both linear and nonlinear kinetic models was also recommended for correct data translations [43][44][45][46][47][48][49][50] .…”
Section: Adsorption Kineticsmentioning
confidence: 99%